2020
DOI: 10.1186/s12889-020-09676-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of postpartum depression among postpartum mothers in central region, Eritrea: a health facility based survey

Abstract: Background Postpartum depression (PPD) is a mood disorder that occurs within the first 12 months after delivery. It affects 20 to 40% of women living in the low-income countries. In resource limited countries discovering the predictors of PPD is important as it allows close follow-up and targeted screening of at risk mothers. The objective of this study was to assess the magnitude and predictors of PPD among recently delivered mothers in Central Region of Eritrea. Methods This study used analytical cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
25
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 35 publications
7
25
4
4
Order By: Relevance
“…Lack of husband or partner support was a strong risk factor on postpartum depression (43,44), and we also observed similar results. We did not observe the associations between family monthly per capita income and postpartum depression, inconsistent with previous studies (45,46). One of the possible explanations is that the data were based on an investigation in urban areas, and the surveyed women have a relatively higher economic level.…”
Section: Discussioncontrasting
confidence: 99%
“…Lack of husband or partner support was a strong risk factor on postpartum depression (43,44), and we also observed similar results. We did not observe the associations between family monthly per capita income and postpartum depression, inconsistent with previous studies (45,46). One of the possible explanations is that the data were based on an investigation in urban areas, and the surveyed women have a relatively higher economic level.…”
Section: Discussioncontrasting
confidence: 99%
“…show that a mother between 35-39 years old has a lower risk of developing postpartum depression and mothers between 40-44 years old have a greater risk of postpartum depression 4 . A study from Gebregziabher explained that housewives had 0,24 times less incidence of postpartum depression than working mothers, but mothers with low economic status had a 13 times greater risk of developing postpartum depression than the good one 5 .…”
Section: Resultsmentioning
confidence: 99%
“…The findings of a similar study showed that the women who had their husband's support for the child care and women who had contented marital relationship had lower risk of having postnatal depression [16]. Another study confirmed the significant association of social support with postnatal depression and suggested that the lack of home support was a contributory factor towards having postnatal depression among puerperal women [17].Gebregziabher et al found the lack of support from husband as a significant risk factor for developing postpartum depression [18]. The logistic regression analysis done by Ozmen et al measured a significant association of perceived social support from significant other and perceived social support from family with postnatal depression, however, no association was found between perceived social support from friends with postnatal depression [19].…”
Section: Discussionmentioning
confidence: 97%